Phylogeography of endemic toads and post-Pliocene persistence of the Brazilian Atlantic Forest - Thome, Maria Tereza C. [UNESP]; Zamudio, Kelly R.; Giovanelli, Joao G. R. [UNESP]; Haddad, Celio Fernando Baptista [UNESP]; Baldissera, Flavio A.; Alexandrino, Joao [UNESP] (Academic Press Inc. Elsevier B.V., 2010)
The Plio-Pleistocene refugia hypothesis recently gained support in explaining Brazilian Atlantic Forest megadiversity from combined analyses of species paleodistributions and genetic diversity. Here we examine genetic differentiation and historical distributions in the Rhinella crucifer group of toads, endemic to and widely distributed within this biome. We analyzed sequences of mitochondrial (control region, ND1, and ND2) and nuclear (beta-crystallin and rhodopsin) DNA markers from 65 individuals representing five species. We found deep structure across the range at mitochondrial markers; genetic diversity is geographically structured in four main haplotype clades with the oldest divergence, dated to the Pliocene, between the southernmost populations and other regions of the species' range. Remaining populations are distributed in haplotype clades that may have diverged throughout the Pleistocene. Our paleoecological distribution models support a scenario of habitat fragmentation associated with glacial cycling, but we found limited congruence of phylogeographic patterns with the refugia. We found that some genetic breaks geographically coincide with putative barriers associated to neotectonic activity, but finer-scale sampling will be necessary to test the relative importance of distinct isolation mechanisms. Overall, the data refute the recently proposed hypothesis of a southern Holocene colonization of the Atlantic Forest from northern refugia, suggesting instead persistence of forested habitats in the south. Our unexpected results underscore the need to consider distinct organismal histories in planning biome-level conservation. We discuss species correspondence to clades recovered in our phylogenetic analyses. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Amphibian; Neotropical; Biogeography; Paleoecological niche modeling; Refugia; Neotectonics